2017
DOI: 10.1111/jels.12162
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Judging on the Federal Courts of Appeals

Abstract: We construct a database of federal appellate cases involving religious liberties decided between 2006 and 2015, expanding and improving an existing database covering up to 2005. The data are used to investigate the role of religion in judicial decision making. We find that Jewish judges are significantly more likely than their non‐Jewish colleagues to favor claimants in religious liberties cases, but we find no significant effects for other minority religions. Our findings confirm previous findings in the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Songer and Tabrizi (1999) find that evangelical state supreme court judges are more conservative across key social issue areas than are mainline Protestant, Catholic, and Jewish judges, while Pinello (2003) analyzes voting on LGBT-rights issues, finding that Jewish judges are more inclined to favor these issues and Catholic judges are less so, both in comparison with Protestant judges. Shahshahani and Liu (2017) provide perhaps the most in-depth examination of religion and judging. Examining federal courts of appeals cases involving religious freedom claims, they find that Jewish judges are more likely to favor claimants; a likely explanation, they argue, is that Jewish judges are more likely to be concerned about the separation of church and state.…”
Section: Other Personal Characteristicsmentioning
confidence: 99%
“…Songer and Tabrizi (1999) find that evangelical state supreme court judges are more conservative across key social issue areas than are mainline Protestant, Catholic, and Jewish judges, while Pinello (2003) analyzes voting on LGBT-rights issues, finding that Jewish judges are more inclined to favor these issues and Catholic judges are less so, both in comparison with Protestant judges. Shahshahani and Liu (2017) provide perhaps the most in-depth examination of religion and judging. Examining federal courts of appeals cases involving religious freedom claims, they find that Jewish judges are more likely to favor claimants; a likely explanation, they argue, is that Jewish judges are more likely to be concerned about the separation of church and state.…”
Section: Other Personal Characteristicsmentioning
confidence: 99%
“…Prior studies have typically attempted to gain purchase on the problem of religious bias by analyzing cases involving allegations of public discrimination, that is, discrimination in which the alleged perpetrator is the government (Heise & Sisk, 2013;Shahshahani & Liu, 2017;Sisk, 2005;Sisk et al, 2004;Sisk & Heise, 2012a, 2012b. These cases can be broadly separated into two categories: Those implicating the Establishment Clause of the First Amendment and those implicating the Free Exercise Clause of the First Amendment.…”
Section: Private Title VII Claims and The Role Of Religionmentioning
confidence: 99%
“…Our analysis builds on a series of previous studies that have already established that evidence for religious bias among judges is sparse, at least in cases involving the government. The most recent of these studies, conducted by Shahshahani and Liu (2017), found that only Jewish judges are more likely than their non-Jewish colleagues to vote in a discernible way and that this phenomenon is "best understood as a secularizing force keen on preserving the separation of church and state, rather than as a protective attitude toward practitioners of minority religions" (p. 718). Furthermore, other scholars have even found evidence to suggest that religious judges are actually "more likely to rule against fellow believers [than claimants of different faiths]" in cases connected to the Free Exercise Clause of the First Amendment or other federal provisions prohibiting governmental discrimination (Heise & Sisk, 2013, p. 1405.…”
Section: Introductionmentioning
confidence: 99%
“…There is reason for some caution here, however, as a recent study found no evidence of panel effects in religious freedom cases brought in the US Federal Courts. 94 In addition to the above, we might imagine other methods by which judges could engage more directly with their religious and other normative priors on an explicit and regular basis. There are, however, challenges specic to the judicial setting in institutionalizing practices that encourage selfconsciousness in other elds.…”
Section: Implications For Judicial Decisionsmentioning
confidence: 99%